Anthropometric factors and non-Hodgkin's lymphoma risk: systematic review and meta-analysis of prospective studies. (September 2018) - Hidayat, Khemayanto; Li, Hui-Juan; Shi, Bi-Min
Abstract: The associations between anthropometric factors and non-Hodgkin's lymphoma (NHL) risk remain inconclusive. A meta-analysis was performed to clarify these associations. PubMed and Web of Science were searched for relevant prospective observational studies. A random-effects model was used to generate the summary relative risks (RRs) with 95% confidence intervals (CIs). A total of 22 prospective cohort studies, with over 20, 000 NHL cases, were included in the present meta-analysis. The summary RRs of NHL risk were 1.06 (95% CI 1.03, 1.09) for each 5 kg/m 2 increase in body mass index (BMI), 1.11 (95% CI 1.07, 1.16) for each 5 kg/m 2 increase in BMI in early adulthood (age 18–21 years), 1.05 (95% CI 1.01, 1.09) for each 10 kg increase in weight, 1.21 (95% CI 1.15, 1.28) for each 10 kg increase in weight in early adulthood (age 18–21 years), and 1.13 (95% CI 1.10, 1.17) for each 10 cm increase in height. No association was found for waist circumference (WC) and waist-to-hip ratio. By subtypes, all anthropometric factors (but not WC) were associated with an increased risk of diffuse large B-cell lymphoma. Chronic lymphocytic leukemia/small lymphocytic lymphoma was positively associated with BMI in early adulthood and with height, whereas follicular lymphoma was only positively associated with height. In summary, BMI and weight in early adulthood may be more relevant to NHL development than current BMI and weight. These findings emphasize the importance of maintaining a healthy weight throughout the life-course, starting from early life, for NHL prevention. Increased NHL risk with taller stature, which may reflect cumulative exposure to hormones/growth factors and nutrition status in early life, further supports the relevance of early life exposure in the etiology of NHL.